Migracja Polaków do Wielkiej Brytanii. Szacunki ilościowe i wstępna charakterystyka demograficzna - Biernat, Joanna (Emmigration of Polish Citizens to The United Kingdom. Estimations of Size and Preliminary Demographical Characteristics, 2008)
The article presents estimations regarding the quantity of emmigration from Poland to the United Kingdom, which has been taking place since the 1st May 2004 and the features of emmigrants. The article describes basic statistical research which makes reference to the emmigration to the United Kingdom and is conducted in this country by Department for Work and Pensions, Office for National Statistics and Home Office.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 201-211